2012
DOI: 10.1002/mren.201200010
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Investigation of Secondary Reactions in Poly(vinyl chloride) Free‐Radical Polymerization

Abstract: Free-radical polymerization of vinyl chloride is investigated computationally with special attention to the secondary reactions involving mid-chain radicals (MCRs). Namely, the rate constants of backbiting, chain scission, chain transfer, and propagation reactions are evaluated using a density functional theory method. The rate coefficients of such reactions are estimated taking into account the position of the radical along the chain as well as its distance from the chain-end. In particular 1:5, 5:1, and 5:9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Studies on this effect on polymerization kinetics, particularly backbiting and propagation of midchain radicals (MCRs), revealed that in steady-state conditions (i.e., at the equilibrium between MCR formation due to backbiting and consumption due to MCR propagation) the fraction of MCRs is inversely proportional to the monomer concentration, as shown by eq : , where Q is the concentration of MCRs, R the concentration of secondary radicals, k bb the backbiting rate coefficient, k p T the propagation rate coefficient of MCRs, and M 0 the initial monomer concentration. Since the two types of radicals are generally characterized by different propagation rate coefficients (i.e., k p T is some orders of magnitude smaller than the corresponding rate coefficient of secondary radicals, k p ), the rate of monomer conversion at a given monomer conversion is affected by a change in the initial monomer concentration. More precisely, an increase in the initial monomer concentration results in an increase in the polymerization rate due to an increase of R with respect to Q , according to eq . Considering a copolymer system, it is easy to show that the rate of copolymerization exhibits the same dependence on the relative amount of the two radicals and thus on the variation in the initial amount of monomer.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on this effect on polymerization kinetics, particularly backbiting and propagation of midchain radicals (MCRs), revealed that in steady-state conditions (i.e., at the equilibrium between MCR formation due to backbiting and consumption due to MCR propagation) the fraction of MCRs is inversely proportional to the monomer concentration, as shown by eq : , where Q is the concentration of MCRs, R the concentration of secondary radicals, k bb the backbiting rate coefficient, k p T the propagation rate coefficient of MCRs, and M 0 the initial monomer concentration. Since the two types of radicals are generally characterized by different propagation rate coefficients (i.e., k p T is some orders of magnitude smaller than the corresponding rate coefficient of secondary radicals, k p ), the rate of monomer conversion at a given monomer conversion is affected by a change in the initial monomer concentration. More precisely, an increase in the initial monomer concentration results in an increase in the polymerization rate due to an increase of R with respect to Q , according to eq . Considering a copolymer system, it is easy to show that the rate of copolymerization exhibits the same dependence on the relative amount of the two radicals and thus on the variation in the initial amount of monomer.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the rate coefficients of propagation reaction of MCRs were estimated for various systems [70,104,142,144]. Furthermore, both the two symmetric breaks of the carbon-carbon bonds that can occur when a MCR undergoes a β-scission reaction were studied [70,106,143,144,151,152].…”
Section: Secondary Reactionsmentioning
confidence: 99%
“…This process pushes the interest towards increasingly complex and fascinating secondary reactions, such as those involving new types of radicals or originating very specific side-products and defects (e.g., side-backbiting producing short-branch radicals and their following propagation) [70,104]. Their kinetic characterization is still out of the reach of the experimental investigation, so this is the field where QC studies find the widest room for application.…”
Section: Secondary Reactionsmentioning
confidence: 99%
“…Density functional theory (DFT) is adopted to evaluate the thermodynamic and kinetic parameters of the investigated reactions . On the basis of previous studies, , the B3LYP functional is primarily applied to perform geometry optimizations and frequency calculations and to detect transition state structures. , Afterward, single-point calculations and energy estimations are performed at the MPWB1K level of theory for the reactants, products, and transition state structures that correspond to the reactions being studied . In the combined B3LYP/MPWB1K approach, the 6-31G basis set with added polarization functions is adopted .…”
Section: Computational Detailsmentioning
confidence: 99%